Improving The Quality of Learning Based on Sustainable Development Goals - Reska Pragusta; Pardiman Pardiman; Djoni Harijanto (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article internalizes the value of Sustainable development of goals (SDGs) into the learning process of MAN 1 Malang. Now MAN 1 Malang is not only being challenged by the old challenges, namely finding Islamic and Indonesian characters and modernization challenges, but also internalizing the SDGS values ​​into the learning process. The research method used is qualitative with the type of case study research. Researchers collected data utilizing in-depth interviews, participant observation, and documentation. While data analysis with data presentation, data condensation, and concluding. As for checking the validity of the data, it is done by using credibility, transferability, dependability, and confirmability techniques. This study resulted in the findings: the development of SDGs-based learning in madrasah aliyah places the basis on intelligence, knowledge, noble character, personality, and concern for the environment. The attitude of concern for the environment includes student behavior in student interpersonal interactions such as honesty, discipline, confidence, caring, and responsibility for oneself, family, and nature according to the main goal of sustainable development of goals.